Some prosodic aspects in hindi - Chandrashekar Prasad Srivastava (Journal of All India Institute of Speech and Hearing, 1970)
Intonation like everything else in language is one instrument in an orchestra. Some consider intonation as only a "peripheral part of communication", whereasaccording to some others intonation is 'central' in communication.